Relokasi Recloser Dengan Metode Section Technique Pada Jaringan Distribusi 20 kV - Samsurizal Samsurizal; Yogi Darul Fadli (Sekolah Tinggi Teknik - PLN, 2021)
The distribution network is the part of the electric power system that is closest to the customer. The reliability of each component of the distribution system equipment can affect the continuity of power service. This study aims to evaluate the reliability of the distribution system at the Citarik Feeder and to improve the system reliability index. The method used is the section technique method and the reliability index values for the Citarik Feeder are obtained, namely SAIFI 1.08958323 faults per customer.year, SAIDI 12.9958323 hours per customer.year. Calculations using ETAP existing conditions, Citarik Feeder SAIFI 1.0679 faults per customer.year, SAIDI 12.9629 hours per customer.year. To increase reliability, a recloser was implemented on the feeder and the most optimal reliability index was obtained, namely, Citarik Feeder SAIFI 0.9885 faults per customer.year, SAIDI 12.8447 hours per customer.year